2020
DOI: 10.1002/agj2.20326
|View full text |Cite
|
Sign up to set email alerts
|

Introducing grazeable cover crops to the winter wheat systems in Oklahoma

Abstract: Fields are typically kept fallow after winter wheat (Triticum aestivum L.) grain harvest in the U.S. southern Great Plains (SGP). Introducing summer cover crops to the system could increase soil conservation and farm profitability if grazed. The objective of this research was to evaluate cover crops' forage yield, residue cover potential, weed suppression, and effect on wheat production. Monocultures and grass-legume mixtures of cover crops were established in mid-June of 2016 and 2017 near Chickasha and Perki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…Conversely, PM+MB mixture had no N-deficient pearl millet plants in Perkins, 2016(Horn et al, 2020. This superior CP concentration in Perkins' PM+MB mixture reinforced Horn et al (2020) assumption that N fixation by mung beans enhanced soil N availability for pearl millet development in N-deficient soils (like Perkins). Other studies also reported that planting legumes with pearl millet improved grass crop development in N-limiting environments in Africa (Gbèhounou & Adango, 2003;Aliyu & Emechebe, 2006).…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Conversely, PM+MB mixture had no N-deficient pearl millet plants in Perkins, 2016(Horn et al, 2020. This superior CP concentration in Perkins' PM+MB mixture reinforced Horn et al (2020) assumption that N fixation by mung beans enhanced soil N availability for pearl millet development in N-deficient soils (like Perkins). Other studies also reported that planting legumes with pearl millet improved grass crop development in N-limiting environments in Africa (Gbèhounou & Adango, 2003;Aliyu & Emechebe, 2006).…”
Section: Discussionmentioning
confidence: 89%
“…However, in Perkins, solely planted pearl millet exhibited N-deficiency symptoms, including plant stunting and yellow leaves. Conversely, PM+MB mixture had no N-deficient pearl millet plants in Perkins, 2016(Horn et al, 2020. This superior CP concentration in Perkins' PM+MB mixture reinforced Horn et al (2020) assumption that N fixation by mung beans enhanced soil N availability for pearl millet development in N-deficient soils (like Perkins).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations